Call for Action: High Rates of Depression in the Pediatric Celiac Disease Population Impacts Quality of Life. Issue 3 (22nd August 2021) - Jericho, Hilary; Khan, Narmeen; Cordova, Jonathan; Sansotta, Naire; Guandalini, Stefano; Keenan, Kate
Abstract : Objective: To test the impact of celiac disease (CD) and depression symptoms on quality of life in adolescent patients. Methods: We conducted a prospective survey of 12- to 18-year-old celiac patients and their caregivers between January 2015 and November 2016. Enrolled parents and youth completed standard measures of adjustment to celiac disease, depression, and quality of life. Results: We enrolled 105 patients with CD and their parents. Both parents and youth reported high levels of depression symptoms. There were no associations between age, duration of CD, or following a gluten-free diet (GFD) and quality of life. No significant associations were found between adolescent perception of CD state and quality of life; parental report of adolescent's adjustment to CD; and youth report of quality of life were modestly associated (r = 0.19, P ≤ 0.05). Moderate associations were observed between adolescent reports of depression and quality of life (r = 0.59, P < 0.01) and between parental reports of adolescent depression and quality of life (r = 0.41, P = 0.01). Only depressive symptoms by youth and parent report, however, and not adjustment to celiac, explained unique variance in quality of life. Conclusion: Adolescents with CD report levels of depression comparable to those reported by adolescents seeking mental health services. Length of time living with CD, or on GFD, age at diagnosis and perception of disease state do not appear to contribute to depression. High rates of depression may impact CD prognosis, therefore, screening for depression in adolescents with CD appears critical. Identification and intervention of depression may lead to improved adherence to the GFD during emerging adulthood.